"TO EVALUATE THE IMPACT OF PLATELET-RICH FIBRIN WITH CONCHAL CARTILAGE GRAFT AND PLATELET-RICH FIBRIN WITH TEMPORALIS FASCIA GRAFT ON ENHANCING AUDITORY FUNCTION FOLLOWING TYMPANOPLASTY: A RANDOMIZED CONTROLLED TRIAL." - Dr. Sanjay Gupta; Dr.Navin Agrawal; Dr. Tanmay Singhai (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Tympanic membrane perforations can lead to significant hearing loss and often necessitate surgical intervention. Conchal cartilage grafts and temporalis fascia grafts are commonly employed in tympanoplasty procedures. Recent advancements suggest that the incorporation of platelet-rich fibrin (PRF) may enhance the healing process [Saluja et al.,2011][1]. Objective: This study aims to evaluate and compare the effectiveness of PRF combined with conchal cartilage graft versus PRF combined with temporalis fascia graft in the repair of tympanic membrane perforations, with a focus on auditory function improvement [Taneja et al., 2020][2]. Methods: This randomized controlled trial involved 100 patients with tympanic membrane perforations. The patients were randomly assigned into two groups, each consisting of 50 patients: Group A received PRF with conchal cartilage graft, and Group B received PRF with temporalis fascia graft. The primary outcome measure was the improvement in hearing function, assessed through audiometric tests pre- and post-operatively [Erkilet et al., 2009][3]. Results: Both groups exhibited comparable demographic characteristics (p-values: age 0.286; gender 0.423). The mean hearing gain was greater in Group 1 (14.63 dB) compared to Group 2 (13.47 dB), although not statistically significant (p=0.32). At three months post-operatively, complete tympanic membrane healing rates were 98% in Group 1 versus 94% in Group 2 (p=0.371) [Nair et al.,2019][4]. Conclusion: The study suggests that PRF combined with conchal cartilage grafts may provide better auditory function restoration and similar healing outcomes compared to temporalis fascia grafts in tympanoplasty. Further research is warranted to explore the clinical implications of these findings in larger populations [Sharma et al., 2018][5].